Lidah Buaya (Aloe vera) Sebagai Obat Herbal Penyembuh Luka - Dewi Permata Sari; Chanseli Siringoringo; Muhammad Komarul Huda (Journal of Natural Sciences, 2022)
This study was carried out with the main objective of explaining the content contained in the Aloe vera plant, and its effect on the healing process of burns. The research was conducted by utilizing various literatures that are in accordance with the topic of this research. The method used in this study is included in qualitative research by collecting various literatures or information and then analyzed to obtain a relationship or linkage with the research. Through the development of this research, it can then be explained that the Aloe vera plant has various benefits, one of which is as a wound healer because Aloe vera contains saponins, tannins, mannose-6-phosphate and polysaccharides. The compounds contained in these plants play an important role in the wound healing process. Aloe vera is a plant that contains active substances that can accelerate wound healing such as glucomannan, lignin, vitamin A, vitamin C, enzymes and amino acids that are important for skin cell regeneration. With a variety of content and benefits in these plants can accelerate wound healing and closure.